2023
DOI: 10.1021/jacs.2c13541
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Covalent Organic Frameworks via a Visible-Light-Activated Photocatalytic Multicomponent Reaction

Abstract: Multicomponent reactions (MCRs), as a powerful one-pot combinatorial synthesis tool, have been recently applied to the synthesis of covalent organic frameworks (COFs). Compared with the thermally driven MCRs, the photocatalytic MCR-based COF synthesis has not yet been investigated. Herein, we first report the construction of COFs by a photocatalytic multicomponent reaction. Upon visible-light irradiation, a series of COFs with excellent crystallinity, stability, and permanent porosity are successfully synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…Furthermore, a broad scope of substrates could be catalyzed by the dimer. This is similar to other catalysts that could work with a broad scope of substrates (Figure B). …”
Section: Resultssupporting
confidence: 83%
“…Furthermore, a broad scope of substrates could be catalyzed by the dimer. This is similar to other catalysts that could work with a broad scope of substrates (Figure B). …”
Section: Resultssupporting
confidence: 83%
“…To confirm the formation of imine linkages in NJU-318 and NJU-319Fe, Fourier transform infrared (FTIR) spectra and solid-state nuclear magnetic resonance (ssNMR) spectra were collected (Figures S4–S7). The diminished CO stretching vibration at 1701 cm –1 of the aldehydes and the appearance of characteristic CN stretching vibrations at 1625 cm –1 for NJU-318 and NJU-319Fe corroborated the formation of imine bonds. Furthermore, the CN peaks (158 ppm for NJU-318 and 159 ppm for NJU-319Fe) in the ssNMR spectra further verified the existence of imine groups in both NJU-318 and NJU-319Fe.…”
Section: Resultsmentioning
confidence: 69%
“…[26] In 2023, Dong et al reported the synthesis of a series of COFs via photocatalytic multicomponent Petasis reaction under visible light irradiation (Figure 8). [27] In the presence of [Ir-(dtbbpy)(ppy) 2 ]PF 6 as the photosensitizer, four different COFs with excellent crystallinity, stability, and permanent porosity termed as Cy-N 3 -COF, Cy-LZU-1, Cy-COF-42, and Cy-TPB-DMTP-COF were constructed via the condensation of potassium cyclohexyltrifluoroborate with different aldehydes and hydrazines or amines or hydrazides using acetic acid as the catalyst in anhydrous 1,4-dioxane under blue LED irradiation for 72 h at room temperature. Furthermore, the obtained Cy-N 3 -COF exhibited excellent photoactivity and recyclability for the photocatalytic oxidative hydroxylation of arylboronic acids with a wide substrate scope.…”
Section: Photocatalytic Reaction Using a Photocatalystmentioning
confidence: 99%